The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1526924817699967
|View full text |Cite
|
Sign up to set email alerts
|

Transcendental Spirituality and Acquaintance With the Activities of the Domestic National Transplant Center as Factors Shaping Attitudes Toward Organ Donation

Abstract: A multifaceted approach to improving attitudes toward organ donation among Jews and Muslim Arabs in Israel is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Only about one‐third of Western Muslims believe that organ donation is compatible with their faith . Studies conducted in Spain, Poland, Israel, and South Africa have found that Muslims are more reluctant to donate their organs compared to adherents of other faiths . In a study comparing attitudes of South Asians in the UK, Muslims reported less favorable attitudes toward organ donation than Hindus or Sikhs .…”
Section: Resultsmentioning
confidence: 99%
“…Only about one‐third of Western Muslims believe that organ donation is compatible with their faith . Studies conducted in Spain, Poland, Israel, and South Africa have found that Muslims are more reluctant to donate their organs compared to adherents of other faiths . In a study comparing attitudes of South Asians in the UK, Muslims reported less favorable attitudes toward organ donation than Hindus or Sikhs .…”
Section: Resultsmentioning
confidence: 99%
“…Ethnicity shapes perceptions of identity and belonging, which, in like manner, shape attitudes toward organ donation. 83 , 84 Religion” is formally defined as believing in a Divinity and feeling a commitment to a specific organized religion. 85 There are 2 major religions in Israel: Judaism, and Islam.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor underlying negative attitudes to organ donation was the feeling of estrangement or not fully being part of the wider society. 83 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each question is scored separately with higher scores representing a higher likelihood of participating towards the intended action. The scale has been used in various studies (e.g., Morgan et al, 2001;Melnikov et al, 2017;Siegel et al, 2014), and is comprised of six items, such as: "I support the idea of organ donation for transplantation purposes," and "I view organ donation as a benefit to humanity." The mean of the scale for participants was 5.82 (SD= 1.37).…”
Section: Attitudes Towards Organ Donationmentioning
confidence: 99%